The Influence Of PAI Learning Outcomes On Students' Characteristics Class VII Mts Negeri 03 Indramayu - Khuzaimah (Beginner: Journal of Teaching and Education Management, 2023)
The purpose of this research is to: (1) Explain the learning outcomes of class VII students of MTS Negeri 03 Indramayu. (2) Describe the morals of class VII MTS Negeri 03 Indramayu. (3) Explaining the effect of PAI learning outcomes on the morals of class VII MTS 03 Indramayu students. This research is a field research with a correlational type quantitative approach. The data collection techniques used were: (1) a questionnaire in the form of collecting data on the morals of class VII students, (2) documentation in the form of draft scores to analyze the morals of class VII students. The results showed that the learning outcomes of students in class VII MTS Negeri 03 were in the moderate category, this was proven from calculations at intervals 68-92 of 32 students with a percentage of 56.10%, (2) The morals of class VII students of MTS Negeri 03 included are in the medium category, this is evidenced from calculations at intervals of 64-86 as many as 48 students with a percentage of 84.20%, (3) There is a significant influence between student Islamic education learning outcomes on the morals of class VII students of MTS Negeri 03 Indramayu. This is evidenced by the obtained tcount value of 4.466 > 1.672 (ttable) and a sig value of student learning outcomes of 0.000 which is 0.000 <0.05 so that Ho is rejected and Ha is accepted, which means that student learning outcomes of PAI partially have a positive and significant effect on morals students of class VII MTS 03 Indramayu.